Strategi Peningkatan Kemampuan Public Speaking Santri Melalui Kegiatan Muhadharah Di Madrasah Diniyah Bani Salim, Ponorogo - Wiwin Rif'atul Fauziyati (Journal of Communication Studies, 2022)
In this modern era, the concept of da'wah also takes part in its innovation. Especially in educational institutions, they declare themselves to provide a curriculum of da'wah strategies to their students. One of the da'wah strategies is through public speaking. One form of output from public speaking in Madrasah Diniyah institutions is muhadhoroh. Muhadhoroh is part of the activities carried out by students in the form of speech bars or lectures whose activities are in public. The implementation of this muhadhoroh activity is so that the class students as adults can have independence and skills in public speaking. In this study using a qualitative method. The form of this method is by exploring and understanding the meaning of a number of individuals or groups as a form of human social problems. Interviews, documentation, and observations are part of the data collection. The data analysis technique is in descriptive form. The results of this study are: 1) Provision of provisions to students about muhadhoroh in the form of theory, 2) The form of public speaking training carried out by students by using lecture and question and answer strategies, and 3) Provision of students when carrying out muhadhoroh by using the memorization method. Keywords: Strategy, public speaking, muhadhoroh, Madrasah Diniyah